A study of the impact of social network types on the health of older adults—Mediated by psychological resilience - Yuan Chai; Qi Zhang; Yifei Yuan (PLoS ONE, 2025)
Aim To explore the different types of social network types and their impact on the health of the elderly, as well as the influencing mechanisms to promote their health. Method k-means clustering, regression analysis, mediating effect method. Results For Chinese elderly people, social network types have a significant impact on the self-rated health, but not on the chronic conditions. The benefits of diverse social network types are significant and positively influence their health by enhancing psychological resilience. There is heterogeneity among different characteristic groups. Discussion This not only suggests that elderly individuals should consciously engage with different types of people in their daily lives, but also emphasizes the need for the government to further establish and improve platforms that promote a diverse social network for the elderly, and provide personalized services and guidance for different groups.